Earnings Response Coefficient as a Measure of Market Expectations: Evidence from Tunis Stock Exchange - MAHJOUBI, Mohamed; ABAOUB, Ezzeddine (International Journal of Economics and Financial Issues, 2015)
This research is a feedback to the call from Richardson et al. (2010) for more structure in researchers’ forecasting frameworks. The purpose is to study the ability of three technical earnings forecasting methods (smoothing, random walk and cross-section) to reflect Tunisian stock market expectations as measured by the Earnings Response Coefficient (ERC). The results of estimating a modified version of Easton & Harris (1991) model that incorporates earnings surprise and its level as return predictors, confirm theoretical predictions on the positive earnings-returns relationship. However, only non-expected earnings are statistically significant. This result indicates a predominance of earnings surprise. Coefficient amplitudes show the subsidiary role of earnings level compared to their surprise in earnings-return regressions. This finding points out the relatively permanent nature of Tunisian firms earnings within Ali & Zarowin (1992)’s context, despite certain exceptions especially with cross-sectional forecasts. Recourse to a quality score based on extreme rankings of examined methods, allowed us to highlight a dominance of smoothing forecasts, followed by those of random walk and finally by the cross-sectional ones. These results corroborate those of Bradshaw et al. (2012) and Gerakos & Gramacy (2013) on the primacy of time series forecasts of earnings and those of Chen and Ho (2014) on the higher explanatory power of earnings changes compared to that of their levels. Keywords: Earnings forecasts; Earnings quality; Earnings Response Coefficients; Fundamental analysis; Market expectations. JEL Classifications: G12; M41